2023
DOI: 10.3390/jimaging9050098
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Satellite Image Analysis for Computing Vegetation Indices by R in the Khartoum Region of Sudan, Northeast Africa

Abstract: Desertification is one of the most destructive climate-related issues in the Sudan–Sahel region of Africa. As the assessment of desertification is possible by satellite image analysis using vegetation indices (VIs), this study reports on the technical advantages and capabilities of scripting the ‘raster’ and ‘terra’ R-language packages for computing the VIs. The test area which was considered includes the region of the confluence between the Blue and White Niles in Khartoum, southern Sudan, northeast Africa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…The biggest algorithmic challenge we face when putting the idea of script-based image processing into practice is pattern recognition, which is also the reason why the GRASS GIS concept was undertaken in this study. This paper builds on and extends our previous research on satellite image processing using scripting algorithms [5,6].…”
Section: Current Research Statusmentioning
confidence: 85%
“…The biggest algorithmic challenge we face when putting the idea of script-based image processing into practice is pattern recognition, which is also the reason why the GRASS GIS concept was undertaken in this study. This paper builds on and extends our previous research on satellite image processing using scripting algorithms [5,6].…”
Section: Current Research Statusmentioning
confidence: 85%
“…Our review also showed that the use of multispectral satellite image analysis for computing vegetation indices has been conducted in many African countries. For instance, changes in the vegetation and the overall health of the environment in the area in the Khartoum, Sudan were computed through the use of multispectral images and derived vegetation indices [ 22 ]. In another study, remote sensing products and services have been employed to support agricultural public policies in Africa, with regard to the common agriculture policy, specifically, subsidy management, by providing accurate crop identification using satellite images [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Remote sensing and the use of satellite imagery play a crucial role in monitoring and managing various aspects of the African continent. Multispectral satellite image analysis’s adoption for computing vegetation indices has been showcased in Africa [ 22 ]. This methodology offers significant observations regarding the fluctuations in vegetation and the overall well-being of the ecosystem in the region.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…In contrast, script-based image processing uses the automation of data processing to derive information from the RS data [98]. An alternative approach is presented by machine learning (ML), which can be used as a descriptor of pixel values and partial replacement of the traditional methods using programming [99,100]. The ML is based on the algorithms of artificial intelligence, which include computer vision and statistical analyses.…”
Section: Softwarementioning
confidence: 99%